Using Iconicity in Two-Tier Grammar Test for Adult Learners: A Cognitive Linguistic Approach - Kartika Eva Rahmawati (English Language and Education Spectrum, 2022)
Learning a foreign language is quite challenging, especially for adults (mothers) at Tambak Lorok Semarang. Their mental space about how to arrange sentences in English cannot be separated from how they arrange sentences in Bahasa Indonesia. Thus, a test is designed in order to facilitate the learners' understanding of the concept of arranging sentences in English well. The aims of this study are to investigate how the learners arrange sentences from Bahasa Indonesia to English and what their basic pattern is for the formation of the sentences. The second is to present an appropriate test for them to measure their understanding in terms of arranging sentences in the target language. Since the test has not been tested yet, the writer used 3 steps of the Research and Design Method by Borg and Gall (2003): Research and Information Collecting, Planning, and Developing a Preliminary Form of Product. There were ten questions in the two-tier grammar test. The writer used descriptive analysis to explain the result. The result shows that the learners arrange the sentences based on Bahasa Indonesia's rules. For the test, the questions on the first-tier use icons or pictures related to the optional answer. The second tier contains the reason why they chose the first tier.